(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay intends to investigate which ecdotic perspectives open today for Gadda’s work, whose editorial life continued after the author’s death, due to the wide gap between what he kept unpublished and what instead it was given to the press, during his difficult and painful lifetime. The recent studies on La meditazione milanese (edited by Gian Carlo Roscioni) and on Racconto italiano di ignoto del novecento, on Un fulmine sul 220 and on La meccanica (edited by Dante Isella) brought out the author’s commitment on philosophy and on the novel, and it revolutionized our knowledge, radically changing our critic approach to his texts. The two major challenges that await future publishers are the vastness of the submerged production and the constant circulation and reworking of the published texts. Gadda’s work will therefore continue to offer an ideal field for the combination of philology and criticism, for its indisputable importance, for the vastness and quality of the surviving documentation, as well as for the experimental tension that animates it: the one that makes Gadda a writer with an "accentuated heuristic position".